Respuesta :
Answer:
-321
Step-by-step explanation:
The new value of x is the old value divided by -3. Since y varies inversely, its new value will be the old value divided by 1/-3, equivalently, multiplied by -3:
(-3)(107) = -321
Answer:
-321
Step-by-step explanation:
We know that x and y varies inversely, and that when y = 107, x = -15
we can represent this in the following table:
y x
107 ⇒ -15
Now we need to know the value of y when x = 5,
y x
107 ⇒ -15
? ⇒ 5
we find the answer by inverse rule of three: multiply the top quantities (107 by -15) and then divide by the remaining amount (5), this is:
107(-15)/5 = -1605/5 = -321